The Effect of Experiential Learning on the Ability to Recognize Patterns and Cooperation in Children Aged 4-5 Years - Imrotul Ummah; Ruqoyyah Fitri; Miftakhul Jannah (National Dong Hwa University, 2025)
The results of initial observations conducted at KB Talia Insan Mulia found that the ability to recognize patterns and cooperation was still underdeveloped. For this reason, the author wants to develop Experiential Learning through playing Maze to improve the ability to recognize patterns and cooperation. The purpose of this study is to determine the effect of experiential learning on the ability to recognize patterns and cooperation in children aged 4-5 years. This study uses quantitative research using experimental methods. This study involved 30 early childhood subjects aged 4-5 years, 14 female subjects or 46.66%, 16 male subjects or 53.34%. The instruments in this study were pattern recognition ability observation sheets and cooperation ability observation sheets. The data analysis technique in this study used descriptive analysis with JASP 0.19.10 and non-parametric statistics with the Mann-Whitney U test. The test result shows that p is smaller than 0.05 which means the hypothesis is accepted. Experiential learning has an effect on the ability to recognize patterns and cooperation in children aged 4-5 years. The experiential learning method is expected can become the main strategy in learning in PAUD.